An Intimate Affair : Women, Lingerie, and Sexuality - Fields, Jill, 1954- (Book collections on Project MUSE., 2007)
Presents the history of twentieth-century lingerie. This book examines the ways cultural meanings are orchestrated by the 'fashion-industrial complex, ' and the ways in which individuals and groups embrace, reject, or derive meaning from these everyday, yet significant, intimate articles of clothing.